Team effectiveness in software development: the role of personality and work factors - Endriulaitienė, Auksė; Cirtautienė, Lina (Business: Theory and Practice, 2021)
Globalization and dynamic economic conditions have exponentially increased the use of virtual work in organizations. Effectiveness in software development teams, therefore, is now a relevant issue in business, psychology or other fields. Despite the uniqueness of software development teams and their work conditions, their effectiveness has not been sufficiently researched to clearly determine how it relates to personality traits, work challenges and the virtualization level. To expand the understanding of the mechanisms that influence team effectiveness in software development, an ecological framework is selected. The purpose of this study is to explore the relationship between personality traits, work factors and team effectiveness within the context of software development teams. Methodology: The exploratory study was conducted in international software development companies operating in Lithuania. Forty-five software development teams (N = 142) filled in the Team task performance scale, Hexaco-PI-R questionnaire and rated perceived work challenges and team virtualization level. The statistical analysis was conducted with SPSS. This survey is an initial stage of a larger project. Findings: Personality traits Conscientiousness and Extraversion relate to team effectiveness. In software development teams the most prevalent work challenges were time zone differences, lack of information when working on a project, and lack of a clear purpose. Lack of information and poor foreign language skills negatively affect team effectiveness. A higher virtualization level is associated with more frequent work challenges (culture and foreign language challenges, time zone differences) and team performance.